Transcriptomic responses of Biomphalaria pfeifferi to Schistosoma mansoni: Investigation of a neglected African snail that supports more S. mansoni transmission than any other snail species. - Sarah K Buddenborg; Lijing Bu; Si-Ming Zhang; Faye D Schilkey; Gerald M Mkoji; Eric S Loker (Public Library of Science (PLoS), 2017)
Biomphalaria pfeifferi is highly compatible with the widespread human-infecting blood fluke Schistosoma mansoni and transmits more cases of this parasite to people than any other snail species. For these reasons, B. pfeifferi is the world's most important vector snail for S. mansoni, yet we know relatively little at the molecular level regarding the interactions between B. pfeifferi and S. mansoni from early-stage sporocyst transformation to the development of cercariae.We sought to capture a portrait of the response of B. pfeifferi to S. mansoni as it occurs in nature by undertaking Illumina dual RNA-Seq on uninfected control B. pfeifferi and three intramolluscan developmental stages (1- and 3-days post infection and patent, cercariae-producing infections) using field-derived west Kenyan specimens. A high-quality, well-annotated de novo B. pfeifferi transcriptome was assembled from over a half billion non-S. mansoni paired-end reads. Reads associated with potential symbionts were noted. Some infected snails yielded fewer normalized S. mansoni reads and showed different patterns of transcriptional response than others, an indication that the ability of field-derived snails to support and respond to infection is variable. Alterations in transcripts associated with reproduction were noted, including for the oviposition-related hormone ovipostatin and enzymes involved in metabolism of bioactive amines like dopamine or serotonin. Shedding snails exhibited responses consistent with the need for tissue repair. Both generalized stress and immune factors immune factors (VIgLs, PGRPs, BGBPs, complement C1q-like, chitinases) exhibited complex transcriptional responses in this compatible host-parasite system.This study provides for the first time a large sequence data set to help in interpreting the important vector role of the neglected snail B. pfeifferi in transmission of S. mansoni, including with an emphasis on more natural, field-derived specimens. We have identified B. pfeifferi targets particularly responsive during infection that enable further dissection of the functional role of these candidate molecules.